HUBUNGAN PENGETAHUAN, SIKAP, DAN MOTIVASI DENGAN KEPATUHAN KONSUMSI TABLET BESI FOLAT PADA IBU HAMIL - Budiarni, Widya; Subagio, Hertanto Wahyu (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2012)
Background: The benefit of giving free iron folic tablets to prevent iron deficiency anemia in pregnancy is often inhibited by the compliance of iron folic tablets consumption in pregnant women. Compliance is a behavior that can be influenced by many factors, such as knowledge, attitude and motivation. The purpose of this study is to determine association between knowledge, attitude, and motivation with compliance of iron folic tablets consumption in pregnant women. Methods: This is a cross sectional study, with 56 pregnant women as sample which are selected by consecutive sampling in Halmahera health center, Semarang. Data of compliancy on iron folic tablets consumption was measured by tablet calculation. Data of knowledge, attitude and motivation are taken from interviews using questionnaire. Bivariate analysis performed by Rank Spearman test. Results: This study showed 41,1% of subjects complied iron folic tablet consumption. The average compliance of iron folic tablet consumption in 10 days is 62.86%. Majority of pregnant women have a good knowledge (50%), good attitude (51.8%) and good motivation (57.1%). This study showed association between knowledge (r = 0.370, p = 0.005), attitude (r = 0.343, p = 0.010), and motivation (r = 0.616, p = 0.000) with compliance of iron folic tablets consumption. Conclusion: Motivation is the most dominant factor. The higher the motivation given Â the more compliance the pregnant women of taking iron folic tablets consumption.